Advancing Social Studies Education: Integrating Artificial Intelligence For Skill Development In Asir's Teachers (Journal of Namibian Studies : History Politics Culture, 2023)
This study aimed to utilize artificial intelligence technologies to enhance the development of twenty-first-century skills among social studies educators in the Asir region. The research employed a descriptive, semi-experimental methodology, utilizing artificial intelligence applications (such as CHAT GPT and NEARPOD) along with cognitive assessment tests and skill scorecards. The findings revealed a statistically significant difference in the average scores of the social studies educators in the sample, both in cognitive testing and skill assessment, before and after the application of the AI interventions, favoring the post-application phase.